2022
DOI: 10.3892/etm.2022.11732
|View full text |Cite
|
Sign up to set email alerts
|

Association between site of infection and mortality in patients with cancer with sepsis or septic shock: A retrospective cohort study

Abstract: Infections are associated with increased mortality in patients with sepsis or septic shock. However, to the best of our knowledge, the influence of the site of infection on patients with cancer remains unclear. The present study aimed to evaluate the association between the site of infection and mortality in patients with cancer and sepsis or septic shock. The present study was conducted in a Lebanon tertiary care centre from July 2010 to April 2015. A total of 176 patients with active cancer presenting to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…32 Although several studies have reported the close relationship between the infection origin and prognosis in sepsis patients, different patient inclusion criteria and comorbidities would have non-negligible impact on the observed endpoint event. [32][33][34][35][36] In this study, the infection site was not associated with mortality, which could be partly explained by the late disease status of involved patients (septic shock) in this study other than the early status in previous data (sepsis). 37,38 Many scoring tools to evaluate the prognosis of patients with sepsis or septic shock, such as SOFA, qSOFA, and SIRS standard, exist.…”
Section: Comparison To the Sofa Scoring Model And Machine Learning Modelcontrasting
confidence: 50%
“…32 Although several studies have reported the close relationship between the infection origin and prognosis in sepsis patients, different patient inclusion criteria and comorbidities would have non-negligible impact on the observed endpoint event. [32][33][34][35][36] In this study, the infection site was not associated with mortality, which could be partly explained by the late disease status of involved patients (septic shock) in this study other than the early status in previous data (sepsis). 37,38 Many scoring tools to evaluate the prognosis of patients with sepsis or septic shock, such as SOFA, qSOFA, and SIRS standard, exist.…”
Section: Comparison To the Sofa Scoring Model And Machine Learning Modelcontrasting
confidence: 50%